Establishing and theorising data analytics governance: a descriptive framework and a VSM-based view. Issue 1 (2nd January 2022) - Baijens, Jeroen; Huygh, Tim; Helms, Remko
ABSTRACT: The rise of big data has led to many new opportunities for organisations to create value from data. However, an increasing dependence on data also poses many challenges for organisations. To overcome these challenges, organisations have to establish data analytics governance. Leading IT and information governance literature shows that governance can be implemented through mechanisms. The data analytics literature is not very abundant in describing specific governance mechanisms. Hence, there is a need to identify and describe specific data analytics governance mechanisms. To this end, a preliminary framework based on literature was developed and validated using a multiple case study design. This resulted in an extended descriptive framework that can aide managers in implementing data analytics governance. Furthermore, we draw on viable system model (VSM) theory to make a theoretical contribution by discussing how data analytics governance can contnue to fulfil its purpose of creating (business) value from data.